2004
DOI: 10.1101/lm.82504
|View full text |Cite
|
Sign up to set email alerts
|

Impaired odor recognition memory in patients with hippocampal lesions

Abstract: In humans, impaired recognition memory following lesions thought to be limited to the hippocampal region has been demonstrated for a wide variety of tasks. However, the importance of the human hippocampus for olfactory recognition memory has scarcely been explored. We evaluated the ability of memory-impaired patients with damage thought to be limited to the hippocampal region to recognize a list of odors. The patients were significantly impaired after a retention delay of 1 h. Olfactory sensitivity was intact.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
24
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(31 citation statements)
references
References 22 publications
7
24
0
Order By: Relevance
“…Accordingly, familiarity recognition in humans seems to be almost limitless even at long retention intervals (Standing 1973), while working memory span has been consistently shown to be limited in humans and monkeys (Luck and Vogel 1997;Beason-Held et al 1999;Levy et al 2003Levy et al , 2004Shrager et al 2008;Heuer and Bachevalier 2011). This makes the DOT a good complement to the odor span task for rodents, to study working memory span in mice.…”
Section: Mice Have a Limited Object Memory Spanmentioning
confidence: 99%
See 2 more Smart Citations
“…Accordingly, familiarity recognition in humans seems to be almost limitless even at long retention intervals (Standing 1973), while working memory span has been consistently shown to be limited in humans and monkeys (Luck and Vogel 1997;Beason-Held et al 1999;Levy et al 2003Levy et al , 2004Shrager et al 2008;Heuer and Bachevalier 2011). This makes the DOT a good complement to the odor span task for rodents, to study working memory span in mice.…”
Section: Mice Have a Limited Object Memory Spanmentioning
confidence: 99%
“…HP lesions generally have no or minor effect on item STM and LTM (Broadbent et al 2004;Ainge et al 2006;Hunsaker et al 2008). Nevertheless, recent accumulating experimental evidence suggests that the HP is indeed involved in item STM when the memory load is increased by the number of items (Cave and Squire 1991;Beason-Held et al 1999;Levy et al 2003Levy et al , 2004Shrager et al 2008;van Vugt et al 2010). Item or digit memory after short-retention interval is, in fact, affected in patients or monkeys with HP damage and in amnesic patients in the condition of high load (Cave and Squire 1991;Levy et al 2003), and HP gamma oscillations increase as humans perform a WM task with increasing number of faces or letters (van Vugt et al 2010).…”
mentioning
confidence: 98%
See 1 more Smart Citation
“…It is important to note that we did not aim to separate the contributions of these context components, but to create a distinct context that may support memory. Nevertheless, previous research suggested that both the memory for odors and the memory for spatial arrangements rely on the hippocampus and adjacent cortices (O'Keefe and Nadel 1978; Burgess et al 2002;Fortin et al 2004;Levy et al 2004). Thus, it is tempting to speculate that there is a common mechanism underlying the impact of stress on odor context-dependent and spatial context-dependent memory enhancement, namely the effect of stress (hormones) on the integrative function of the hippocampus.…”
mentioning
confidence: 94%
“…It critically depends on the integrity of the hippocampus and adjacent cortex. 50,91 In a previous study, patients with damage limited to the hippocampal region were impaired at both visual and olfactory memory tasks. 51 The advantage of the social odor novel recognition test is that it uses the rats' primary sensory modality (olfaction) coupled with the social significance (from conspecifics) of the odors to produce strong, long-lasting odor discrimination and memories.…”
Section: Discussionmentioning
confidence: 99%